8t-12=4(2t-3)

Simple and best practice solution for 8t-12=4(2t-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8t-12=4(2t-3) equation:


Simplifying
8t + -12 = 4(2t + -3)

Reorder the terms:
-12 + 8t = 4(2t + -3)

Reorder the terms:
-12 + 8t = 4(-3 + 2t)
-12 + 8t = (-3 * 4 + 2t * 4)
-12 + 8t = (-12 + 8t)

Add '12' to each side of the equation.
-12 + 12 + 8t = -12 + 12 + 8t

Combine like terms: -12 + 12 = 0
0 + 8t = -12 + 12 + 8t
8t = -12 + 12 + 8t

Combine like terms: -12 + 12 = 0
8t = 0 + 8t
8t = 8t

Add '-8t' to each side of the equation.
8t + -8t = 8t + -8t

Combine like terms: 8t + -8t = 0
0 = 8t + -8t

Combine like terms: 8t + -8t = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 3x-x^2=20 | | 6i+3=-7 | | P=14*(8/t) | | -8u-15=15 | | -25t+7t^2-12=0 | | 4(n+6)-2n=3(n+3)-11 | | 7+30x=20x+23 | | 5*(4-9*2)-2*(3*2+4)+7= | | 3w^6*v^9*2v^4*7w=0 | | 32=X-5 | | y=0.5+-1.5y+1 | | 64=l-4 | | 3w^6*v^8*2v^4*7w=0 | | 40/(-5) | | 250=9x-38 | | 6z-30= | | 21x^2+50xy-16y^2=0 | | -0.8n=40 | | Z/3=z—2 | | Y(x+1)-4(x+1)= | | -.125c=2 | | x+2x+3x+4=40 | | 16x=256/x | | 8-3x+7x=-12 | | 4x+40+3x=180 | | m=-1/2;(-4,7) | | (3-u)(3u-2)=0 | | 9ln(x+18)-6ln(x)= | | y=4(0.5) | | -(4y-5)(5y-8)= | | X^2+3x=49 | | 6x^4+40x^3y-14x^2y^2=0 |

Equations solver categories